The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jretconser.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese food retailers – Exploring three classic theories of retail location

Abstract: This article sets forth results from an exploratory empirical study that aimed to test the predictive validity of three classic location theories: central place theory, spatial interaction theory and the principle of minimum differentiation. Correlation, linear regression and analytical procedures in a Geographic Information System were used to reveal relationships between variables. The results show that all theories find significant support. It was possible to relate store location with distance to the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…In the existing literature, many techniques for assessing the determinants of location decisions are based on the use of quantitative variables measured in numbers [17,30] or qualitative variables modelled and categorized by crisp numbers [32]. These traditional methods of gathering information cannot capture the hesitancy or imprecise nature of some linguistic variables.…”
Section: Discussionmentioning
confidence: 99%
“…In the existing literature, many techniques for assessing the determinants of location decisions are based on the use of quantitative variables measured in numbers [17,30] or qualitative variables modelled and categorized by crisp numbers [32]. These traditional methods of gathering information cannot capture the hesitancy or imprecise nature of some linguistic variables.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the issue, retail location decision has become the subject matter of different disciplines such as marketing, urban sciences, economics, geography, applied mathematics and geomarketing and different retail location theories, models and procedures have been proposed. In this sense, it is possible to say that retail location theory is comprised of four broad theoretical areas that are central place theory, spatial interaction theory, land value theory and the principle of minimum differentiation [38,[40][41][42][43][44][45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, the disadvantages or problems of an initially wrong decision in retail store location are extremely difficult to overcome as the location decision represents a long-term, fixed investment which is immobile and unique [37][38][39].Given the importance of the issue, retail location decision has become the subject matter of different disciplines such as marketing, urban sciences, economics, geography, applied mathematics and geomarketing and different retail location theories, models and procedures have been proposed. In this sense, it is possible to say that retail location theory is comprised of four broad theoretical areas that are central place theory, spatial interaction theory, land value theory and the principle of minimum differentiation [38,[40][41][42][43][44][45].Central place theory provides a powerful explanation of the spatial structure of retail facilities and considers the behavior of consumers and retail firms in a spatial market. In the framework of this theory, distance to the supply point and transportation costs are the most important factors.…”
mentioning
confidence: 99%
“…Some authors have analyzed the three classic location theories: central place theory, spatial interaction theory, and the principle of minimum differentiation in the retail sector. Reigadinha et al (2017) have used a GIS to analyze these theories in a geographical area and concluded that decisions related to store location are related to the population density, since the larger the population density the smaller the store's distance from the center, and the larger the center the larger the market area and the store density.…”
Section: Geographic Information Systems (Gis)mentioning
confidence: 99%